Psychophysiological research in real-world environments: methodological perspectives from the SLU Multisensory Outdoor Laboratory - Gunnar Cerwén; Gunnar Cerwén; Caroline M. Hägerhäll; Caroline M. Hägerhäll (Frontiers in Psychology)
Growing evidence demonstrates the importance of environmental quality for human health and wellbeing. Environmental psychology can inform planning and design of future environments, but previous research often used simulated settings, limiting ecological validity. To bridge this gap and enable studies in real environments, a new laboratory (SENSOLA) has been built at the Swedish University of Agricultural Sciences. The laboratory is designed to facilitate studies on human-environment interactions in real environments, with a particular focus on psychophysiology using wearable sensors. An important prerequisite of the endeavor is the ability to synchronize environmental data with biomarkers and participants’ self-reports over time. In this methodological paper, we describe the creation and implementation of the SENSOLA laboratory. Drawing on experiences gained from the first ten studies conducted within the laboratory, we summarize key considerations for conducting research in field settings. We discuss various methodological approaches and procedural considerations, highlighting challenges and possibilities, to serve as a peer-reviewed guideline for future studies in the lab and elsewhere.